Comparison of Selective Catalytic Reduction Performance of Mn–Co Bi‐Metal Oxides Prepared by Different Methods. Issue 30 (11th August 2020) - Yang, Chen; Tang, Xiaolong; Yi, Honghong; Gao, Fengyu; Zhao, Shunzheng; Zhang, Runcao; Zhu, Wenjuan
Abstract: In this work, the low dimensional flake Mn4 Co1 Ox composite oxides were prepared by four different methods (hydrothermal, template, co‐precipitation and one‐step, noted as HS, TM, OP and OS, respectively) and used for the ammonia selective catalytic reduction (NH3 ‐SCR) at low temperatures. The results showed that the activity of the catalysts decreased in the sequence: Mn4 Co1 Ox ‐HS > Mn4 Co1 Ox ‐TM > Mn4 Co1 Ox ‐OP> Mn4 Co1 Ox ‐OS. The activity of the best catalyst (Mn4 Co1 Ox ‐HS) was nearly 100 % NO conversion in the temperature range of 75–250 °C and the N2 selectivity remained above 50 % even at 250 °C. Mn4 Co1 Ox ‐TM catalyst also maintained the NO conversion more than 90 % in the range of 100–250 °C, but the N2 selectivity was poor. The catalytic activity of the other two catalysts was slightly lower than the above two catalysts. Based on the comprehensive characterization, it was found that the Mn4 Co1 Ox ‐HS catalyst had a higher NH3 adsorption and activation capacity, which was attributed to the higher surface area caused by its approximately two‐dimensional folded layered structure leading to more active sites. Meanwhile, it was rich in the surface acid sites, Mn 3+, Co 3+ and surface oxygen in the Mn−Co spinel structure, thus giving strong acidity and good redox capacity. Abstract : In this work, we used four methods to prepare flaky Mn4 Co1 Ox catalysts. And we found the Mn4 Co1 Ox ‐HS catalyst prepared by hydrothermal method has the best NH3 ‐SCR activity. Mn4 Co1 Ox ‐HS had a two‐dimensional morphology with pores, which might provide more active sites for gas molecules to participate in the catalytic process. Simultaneously, it had Mn−Co spinel structure with abundant surface acid sites, Mn 3+, Co 3+ and surface oxygen, and had high NH3 adsorption and activation capacity, as well as good redox capacity.